Inovasi Pembelajaran Pendidikan Agama Islam Penggunaan Media Digital di SMA PAB 4 Sampali - M, Mayzura (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the innovation of Islamic Religious Education (PAI) learning through the use of digital media at SMA PAB 4 Sampali. The background of this research is based on the development of information technology, which requires teachers to adapt to more creative and interactive learning methods and media. This study employs a qualitative method with a library research approach, while the data analysis technique used is content analysis. The results indicate that the use of digital media can help students understand the material more easily, increase learning motivation, and encourage independent learning. However, challenges remain, such as limited facilities and technological skills among some teachers and students. Overall, learning innovation through digital media has a positive impact on the effectiveness and quality of Islamic Religious Education at SMA PAB 4 Sampali.